Elemente de credință și practică reflectate în cântările educative ale sabatarienilor transilvăneni din secolul al XVI-lea - Hunor Sándor Nagy (TheoRhēma)
Transylvania’s religious history features a signiﬁcant Sabbatarian movement from the 16th century until the Second World War. Members of this group stood out and were persecuted due to their unique beliefs about the Sabbath and other practices. Beyond understanding how they decided to observe the Sabbath, exploring their core beliefs is essential. They created manuscripts containing their literary works, such as psalms, sermons, letters, and songs. Notably, 15 educational hymns oﬀer valuable insights into their core beliefs and practices. This study seeks to identify and analyze key beliefs and primary practices, tracing their development from a Christian perspective to a Unitarian faith, and ﬁnally, to their distinctive Christian-Jewish faith.